Unreliable ally: participation of the Russia in the war of 1809 against Austria - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2021)
The article reveals the problem of the participation of the Russian Empire in the war of 1809 against Austria, which is little studied in historiography. It is shown that Russia considered Austrian Galicia as its geopolitical field (historical heritage), and therefore opposed its possible inclusion in the Duchy of Warsaw. It is noted that the Russian army, despite allied commitments to France, crossed the border only with the threat of the occupation of Galicia by Polish troops. At the same time, she was passive in actions against Austria (in order to preserve good-neighborly relations), and shied away from helping the Poles. All this led to a tense relationship between the Russian and Polish troops. The article traces in detail the course of hostilities, reveals the mood in Russian army circles (discontent in the officer corps and the escape of soldier). It is shown that the events of 1809 had a significant impact on the aggravation of the situation in the western provinces of the Russian Empire. In general, it is concluded that Russia’s participation in the war against Austria has undermined its image in Europe and contributed to the strengthening of French influence, but only in the short term.
Keywords: war of 1809; Galicia; the Russian Empire; Austrian Empire; Napoleon; Duchy of Warsaw; S. F. Golitsyn; J. Ponyatovsky